Nanoscale phenomena : basic science to device applications - Tang, Zikang (Springer, 2017)
Nanotechnology is the result of the continuing technological trend toward device miniaturization and the characterization, manipulation, and fine control of structure and function at diminishing length scales. A large class of nanoscale materials can be stable even though they are far from the lowest-energy thermodynamic state, and many possess novel properties unattainable in bulk. These trends are supported by the increasing sophistication of characterization and fabrication tools such as the scanning tunneling microscope and the transmission electron microscope, which allow the resolution and manipulation of single atoms and molecules. Nanoscale Phenomena: Basic Science to Device Applications presents selected lectures from the Third Workshop of the Croucher Advanced Study Institute on Nano Science and Technology, and showcases contributions from world-renowned researchers. Chapters fall into four major categories: Nanostructured Carbon and its Applications, Quantum Dots and Molecular Spintronics, Nanomaterials Design and Synthesis, and Molecular Electronics.